(untitled) (Modern Problems of Metallurgy, 2020)
The results of computer simulation of the equilibrium state thermodynamics in a complex heterogeneous Mn-Si-Fe-Ca-Al-Mg-O-P-S-C system for the production of silicomanganese in high-capacity furnaces based on data "HSC 2.03" and "TAPR" Concern "Outokumpu" and the American company "ESMicroware Inc.". It is shown that in the temperature range 1600-1800 оС in the four-phase system "gas-metal-slag-coke" the temperature increase has little effect on the equilibrium content of CO, CO2 and SiO2 in the gas phase, and in the slag phase the temperature increase lowers the concentration of silicon oxide, and The concentration of Mn, Fe, P and Si increases in the metallic phase and the carbon content decreases. Thermodynamic calculations have established the effect of temperature and carbon consumption on the extraction of Mn, Si and the coefficients of their distribution. Statistical processing of the obtained data confirms their high reliability and reliability to correlation coefficients of 0.91-0.98. To optimize the variable parameters, an artificial function is obtained that describes the extraction of manganese, silicon, and the minimum phosphorus content as a function of temperature and carbon content.